2000
DOI: 10.1038/sj.sc.3101022
|View full text |Cite
|
Sign up to set email alerts
|

The value of the Kurtzke Functional Systems Scales in predicting incomplete bladder emptying

Abstract: Study design: A ®eld study was conducted in 40 patients with multiple sclerosis (MS) by comparing their residual urine volumes with the Kurtzke Functional Systems Scales for pyramidal (PFS) or bladder functions (BFS). Objectives: To determine whether raised residual urine volumes necessitating intermittent self catheterisation can be predicted by the PFS or BFS. Setting: Department of Uro-Neurology, The National Hospital for Neurology and Neurosurgery, University College London Hospitals Trust, London, UK. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
9
0
4
Order By: Relevance
“…Few and heterogeneous studies have investigated the relationship between subjective urinary complaints and objective urological parameters in MS patients, reaching different conclusions [3,[5][6][7][8][9]. Is a routinary evaluation of urinary symptoms sufficient to exclude the presence of bladder dysfunction in patients with MS?…”
Section: Introductionmentioning
confidence: 99%
“…Few and heterogeneous studies have investigated the relationship between subjective urinary complaints and objective urological parameters in MS patients, reaching different conclusions [3,[5][6][7][8][9]. Is a routinary evaluation of urinary symptoms sufficient to exclude the presence of bladder dysfunction in patients with MS?…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between MS duration and adverse urodynamic fi ndings (detrusor overactivity, detrusor hypocontractility, DSD) has been demonstrated [6][7][8]19]. Irritative symptoms and neurovesical dysfunction have been correlated with EDSS scores [6,17,[19][20][21], individual Kurtzke Functional System Scales scores [19,22], Babinski sign [8], and lower limb spasticity [17,22]. Therefore, any history of ataxia, gait disturbance, unexplained lower extremity weakness, numbness, or paresthesias suggests concomitant urologic symptoms and may signal occult VUD.…”
Section: Bladder and Urethramentioning
confidence: 99%
“…Two studies have specifi cally focused on the offi ce-based PVR measurement in MS patients [18,22]. Kragt et al [18] studied 297 patients with MS and found that 17% with pyramidal function scale scores of 1 or lower had clinically relevant PVRs.…”
Section: Physical Examinationmentioning
confidence: 99%
“…La prévalence des TVS cliniques apparaît corrélée avec la sévérité des déficiences globales (score EDSS, échelle de Kurtzke) [5,6,9,20,32,33], et celle des symptômes irritatifs est également corrélée avec la sévérité de l'atteinte pyramidale (signe de Babinski, score pyramidal de l'EDSS) [5,9,20]. La corrélation entre la rétention urinaire et le statut neurologique reste débattue [34,35].…”
Section: Analyse De La Littératureunclassified